Analysis of the Critical Thinking Skills of Students in Senior High School in Solving the Reaction Rate Problem - Ramadhan , Moh. R.; Ijirana, Ijirana (Universitas Tadulako, 2023)
This study aimed to obtain a description of the critical thinking skills of SMA Negeri 3 Palu students in solving reaction rate problems. The type of research used is descriptive-quantitative, with the research design in the form of case studies. The research sample consisted of students of class XI IPA 1 to XI IPA 4 SMA Negeri 3 Palu, with 108 students. The research instrument used is a critical thinking skill test in the form of 6 questions, validated with a value obtained for expert validation of 3.72 and an average empirical validation value of 0.72. Data analysis is done by calculating the grades students get for each indicator of critical thinking skills, then grouping them by essential categories of thinking. According to Ennis, the indicators of critical thinking skills used in this study are to provide simple explanations, build basic skills, draw conclusions, provide further explanations, and set strategies and tactics. Based on the results of the research data analysis, the highest percentage of critical thinking skills for the five indicators used in a row, namely 37.04, 51.85, 61.11, 53.70, and 42.59 %. These results show that each student has different critical thinking skills. The percentage obtained is, on average, in the medium to high category. The results of this study show that the essential thinking skills of high school students of SMA Negeri 3 Palu, grade XI IPA, are in a good category.